The Effect of Budget Participation and Organizational Commitment on Budgetary Slack - Agustina, Duwi; Suhaidar (Indonesian Journal of Social Science Research, 2021)
This study aims to measure the effect of employee participation in budgeting and organizational commitment to budgetary slack in Bangka Belitung Islands Provincial Government Agencies, in particular the Public Works and Spatial Planning Office of the Bangka Belitung Islands Province. The analytical method used for testing the variables in this study uses PLS (Partial Least Square) using Smart PLS.3 software. The sample used in this study were 50 employees at the Department of Public Works and Spatial Planning of the Bangka Belitung Islands Province. The first hypothesis in this study is accepted, namely budget participation has a positive effect on budgetary slack, but the second hypothesis in this study is rejected, namely organizational commitment has a negative effect on budgetary slack. This identifies that the participation of many parties in a company or scope of work to jointly exchange information in determining and compiling a budget to achieve an organizational goal.